2018
DOI: 10.1088/1361-6595/aaebdb
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms responsible for the initiation of a fast breakdown in an atmospheric discharge

Abstract: The initial stage of the fast electrical breakdown of an air gap with a pin-to-plane electrode geometry is studied on a nanosecond time scale using multi-frame laser probing with an exposure time of 70ps and spatial resolution as high as 3-4μm. We find that the gap breakdown is associated with the fast (1 ns) formation of a micron-sized (∼10 μm) cathode spot that appears as a plasma with an electron density of » n 10 cm e 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…It should be noted that in a number of works [33,34], it is assumed that the discharge constriction is the result of magnetic compression of plasma channel. The magnetic pressure P m is a function of the discharge current I and of the filament radius R f :…”
Section: Synchronized Electron Temperature and Electron Density Measumentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that in a number of works [33,34], it is assumed that the discharge constriction is the result of magnetic compression of plasma channel. The magnetic pressure P m is a function of the discharge current I and of the filament radius R f :…”
Section: Synchronized Electron Temperature and Electron Density Measumentioning
confidence: 99%
“…In [33] the initial stage of nanosecond discharge at atmospheric pressure was studied with extra-high spatial (3-4 µm) and temporal (70 ps) resolution. The authors demonstrated, that nanosecond breakdown initiated by 4 ns rise time 25 kV amplitude voltage pulse in 3 mm pin-to-plane gap starts from a dense spot of electrons near the cathode, with a density n 0 e > 10 20 cm −3 and a typical size of ∼ 10 µm.…”
Section: Near-electrode Processes and Filament Propagation As An Ionimentioning
confidence: 99%
See 1 more Smart Citation
“…Microchannels in the plasma of pulsed discharges in atmospheric air in tip-plane gaps of a few millimeters long was also found in [14][15][16] for both voltage pulse polarities. Therewith, jets with a high concentration of ionized particles were detected near the electrodes in the case of spark breakdown.…”
Section: Introductionmentioning
confidence: 70%
“…Finally, apart from the EWE, the problem of the droplet origination is also related with the origination of plasma spots at electrodes during gas and vacuum discharges. For instance, when probing the near-electrode plasma formed after the breakdown in small air gaps, some plasma areas turn out to be opaque to 0.532 µm radiation [34][35][36]. Combined with the analytical considerations, the experimental facts point to the existence of dense near-electrode plasma jets generated in electrode local regions due to multiple explosions.…”
Section: Discussionmentioning
confidence: 99%